2014
DOI: 10.1007/978-3-662-45391-9_46
|View full text |Cite
|
Sign up to set email alerts
|

Decidability and Complexity of Simulation Preorder for Data-Centric Web Services

Abstract: In this thesis we address the problem of analyzing specifications of data-centric Web service interaction protocols (also called data-centric business protocols). Specifications of such protocols include data in addition to operation signatures and messages ordering constraints. Analysis of data-centric services is a complex task because of the inherently infinite states of the underlying service execution instances. Our work focuses on characterizing the problem of checking a refinement relation between servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This includes datacentric business processes (e.g., [4,18]) and Web services and applications [2,22], and the analysis goals vary from verification of fully specified processes to the automatic synthesis of new processes combining a given set of components. The results obtained in these lines of research are not applicable to our needs since no provenance model was proposed there.…”
Section: Related Workmentioning
confidence: 99%
“…This includes datacentric business processes (e.g., [4,18]) and Web services and applications [2,22], and the analysis goals vary from verification of fully specified processes to the automatic synthesis of new processes combining a given set of components. The results obtained in these lines of research are not applicable to our needs since no provenance model was proposed there.…”
Section: Related Workmentioning
confidence: 99%
“…We have shown in our previous works [2,3] how to extend the automata-based service composition approach to the case of infinite alphabets, also showing an EXPTIME solution for solving simulation preorder. Akroun et al [1] further demonstrate that it is EXPTIME-complete. However, we also provide a simpler proof of the EXPTIME-completeness claim in this paper.…”
Section: Introductionmentioning
confidence: 98%
“…Akroun et al have used such classes of automata over infinite alphabet to model verification and synthesis problems for Web Services, and give a detailed study in [1]. Parametrized automata, a class of automata introduced by the authors, is shown to be equivalent to finite memory automata with nondeterministic reassignment (NFMAs) [11] in terms of the class of languages they can represent.…”
Section: Introductionmentioning
confidence: 99%